Le 30 regole per la leadership in sanità - Saint, Sanjay (Studi e saggi, 2022)
Thirty Rules for Healthcare Leaders is the essential guide for everyone in healthcare, from those just starting their careers to those who are established leaders. The authors have been in leadership roles within healthcare systems for several years, and have carefully studied healthcare leadership during site visits to hospitals around the world. The book presents practical and timely advice packaged in pithy "pearls" that can be used by time-pressured professionals. Original artwork makes each rule memorable. Meant to be read in one sitting, or one at a time, Thirty Rules for Healthcare Leaders speaks to a broad range of healthcare professionals, regardless of title or experience. If you work in healthcare, this is your new must-read book.